FURTHER BULLAE FROM SELEUCIA ON THE TIGRIS. (17th March 2015) - Messina, Vito
Abstract : This paper makes available clay sealings found during the last campaigns of the Italian expedition at Seleucia on the Tigris whose publication was delayed by the 1990–91 Gulf War. The sealings were discovered in the North Agora—where a large archive building containing more than 25, 000 sealings was also unearthed—and provide additional information on the iconography and style of the subjects impressed on their surfaces by official and private seals. Most of the sealings were found in the context of the stoa, a public building facing the archive on the opposite side of the agora, but seem to have been displaced there accidentally or for some reason, difficult to ascertain, only at a later date: originally they were probably kept in the archive building itself.